2003
DOI: 10.1001/archsurg.138.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Resection in the United States

Abstract: Background: Hepatic resection has become common in the United States for both primary and secondary hepatic tumors. Hypothesis: Variation in outcomes after hepatic resection is related to patient characteristics, the indication for operation, and hospital procedural volume. Design: Observational study using a nationally representative database. Patients: All patients in the Nationwide Inpatient Sample for 1996 and 1997 with a primary procedure code for hepatic resection (N = 2097). Main Outcome Measures: Outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(66 citation statements)
references
References 35 publications
4
56
0
Order By: Relevance
“…In-hospital mortality in this cohort was 4.8%, similar to other population-based studies in HPB procedures. 1,2,8,15,16 HPB surgery most commonly is performed at large hospitals. We found that other demographic factors such as age, public insurance and race may affect surgical results as others have shown from different surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…In-hospital mortality in this cohort was 4.8%, similar to other population-based studies in HPB procedures. 1,2,8,15,16 HPB surgery most commonly is performed at large hospitals. We found that other demographic factors such as age, public insurance and race may affect surgical results as others have shown from different surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in anesthetic techniques and post-operative care led to decreased mortality rates after liver surgery of less than 3% in experienced liver surgery centers [13,14,15]. With these improvements, indications for liver resection are expanding and more patients with liver metastases undergo surgical treatment [3,16].…”
Section: Introductionmentioning
confidence: 99%
“…Benign liver tumors affect up to approximately 20% of the US population [1] and are the indication for hepatic resections in about 6% of patients [2]. No randomized clinical trials were found regarding elective surgery for benign liver tumors; most reported studies are retrospective or include case series with less than 60 patients [3].…”
Section: Introductionmentioning
confidence: 99%